Damp and mould—the big picture. How do we tackle the damp and mould crisis in social housing: lessons from the UK - Benton, Eleanor (Frontiers in Environmental Health, 2024)
The tragic death of two-year-old Awaab Ishak, from extensive and prolonged exposure to damp and mould that had not been dealt with by the social landlord who owned the property, and other high profile news stories, have alerted social landlords to the damp and mould crisis in social rented homes across England. This paper discusses the findings from a 24-hour knowledge exchange ‘Think Tank’, attended by representatives from social housing providers, charities, professional bodies, and residents from across England, to discuss how to tackle damp and mould in social housing. The event was made up of short informal presentations and group discussions in order to share good practice and develop a cross-sector understanding of damp and mould, its impacts, and how it can be tackled holistically. The event highlighted that damp and mould should firstly be seen as a building problem and that residents’ ‘lifestyles’ should not be blamed. Tackling damp and mould should not be seen as the responsibility of one individual or department, all stakeholders need to work together to tackle the problem, ensuring tenants’ wellbeing is at the centre of every decision. Finally, damp and mould cannot be tacked in silo. Social landlords are facing a number of other major challenges, including the cost-of-living crisis, new building safety regulations, and the urgent need to decarbonise their stock. Landlords must think creatively in order to tackle these problems together and consider the big picture to ensure we are not walking towards the next housing tragedy. This paper brings together a wider contextual understanding of how the damp and mould crisis has developed in the UK, the impacts of damp and mould on residents’ physical and mental wellbeing, and the Think Tank findings, to suggest policy and practical recommendations for tackling the problem holistically.